ETOS KERJA DALAM EKONOMI GLOBAL (KASUS MASYARAKAT MUSLIM MELAYU PALEMBANG) - Ritawati, Raden Ayu (Universitas Islam Negeri Raden Fatah Palembang, 2018)
The purpose of this research is to know the influence of Malay and Islam in shaping the social character of Palembang Malay workers in global economic development. The Islamic economic norms embedded and rooted in the local social identity of the local Malays are the key determinants of evaluative aspects of a judging nature. This research departs from the reason as Ushul Fiqih's written adage says